Sleep pattern and locomotor activity are impaired by doxorubicin in non-tumor-bearing rats - Lira, Fabio Santos [UNESP]; Esteves, Andrea Maculano; Pimentel, Gustavo Duarte; Rosa, José Cesar; Frank, Miriam Kannebley; Mariano, Melise Oliveira; Budni, Josiane; Quevedo, João; Santos, Ronaldo Vagner Dos; De Mello, Marco Túlio (Thieme, 2016)
Purpose We sought explore the effects of doxorubicin on sleep patterns and locomotor activity. To investigate these effects, two groups were formed: a control group and a Doxorubicin (DOXO) group. Methods Sixteen rats were randomly assigned to either the control or DOXO groups. The sleep patterns were examined by polysomnographic recording and locomotor activity was evaluated in an open-field test. Results In the light period, the total sleep time and slow wave sleep were decreased, while the wake after sleep onset and arousal were increased in the DOXO group compared with the control group (p<0.05). In the dark period, the total sleep time, arousal, and slow wave sleep were increased, while the wake after sleep onset was decreased in the DOXO group compared with the control group (p<0.05). Moreover, DOXO induced a decrease of crossing and rearing numbers when compared control group (p<0.05). Conclusions Therefore, our results suggest that doxorubicin induces sleep pattern impairments and reduction of locomotor activity.
Keywords: Doxorubicin; Locomotor activity; Rats; Sleep